STEM Education and Problem-Solving in Space Science: A Case Study with CanSat - José Contente; Cecília Galvão (MDPI AG, 2022)
Research has shown that hands-on projects promote stem education, namely via problem-solving. CanSat, literally 'satellite in a can', is a stem educational project promoted by the European Space Agency. This paper addresses this issue by researching this STEM project and trying to understand how secondary students solve problems in the STEM CanSat project. We use qualitative techniques of data collection and analysis. The results showed that students used sophisticated thinking strategies to process information within this interdisciplinary project: (a) cognitive testing, cognitive organization, cognitive regulation, and monitoring, in addition to computer language and physical-mathematical calculations, are cognitive and metacognitive behavior strategies revealed in the CanSat; (b) problem-solving was suggested as a specific model, where students' higher cognitive and metacognitive ordering processes deepen in project development; (c) computational, lateral, or divergent and convergent thinking were detected as thinking types of students associated with and mobilized in the course of problem-solving. The findings of this research have practical implications for STEM education in space science. Hands-on projects using problem-solving are an essential strategy to promote STEM. This project reinforces this. Additionally, they are a starting point to promote meaningful learning and new thinking types.